Wagner and the Romantic hero - Williams, Simon 1943- (Cambridge University Press, 2004)
Few major artists have aroused the ire and adulation of successive generations as persistently as Richard Wagner. He was the centre of controversy during his lifetime and yet, when he died, he was the most idolized man in Germany. The situation has not changed much since then. Simon Williams explores the reasons for this adulation and antipathy by examining an aspect that may be a fundamental cause for this radical division in the reception of Wagner's work, the phenomenon of heroism. Williams analyses this heroism as a function of Wagner's theatre and music, beginning with a definition and examination of the concept of the heroic. The book also discusses all thirteen stage works by Wagner and the phenomenon of heroism and Wagner's adaptation of the figure of the Romantic hero. Williams offers a theatrical, musical, and cultural re-evaluation of one of the most enduring figures in the arts